Ultra-low density three-dimensional nano-silicon carbide architecture with high temperature resistance and mechanical strength. (30th August 2020) - Hart, Amelia H.C.; Owuor, Peter Samora; Hamel, John; Bhowmik, Sanjit; Asif, S.A. Syed; Gentles, Anieph X.; Ozden, Sehmus; Tsafack, Thierry; Keyshar, Kunttal; Mital, Rahul; Hurst, Janet; Vajtai, Robert; et al.
Abstract: Silicon carbide nanotube/nanowires (SiCNT/NWs) exhibit excellent mechanical properties in extreme thermal and oxidative environments. Here, we demonstrate an easily scalable process to synthesize millimeter-sized three-dimensional architectures using SiCNT/NW building blocks to create materials with excellent mechanical strength, stiffness, and resiliency with ultra-low density. The structure of these macro-materials is initially synthesized using carbon nanotubes, then utilizing the shape memory synthesis (SMS) method are converted to nano-silicon carbide. It is proposed that using this technique, any micro-structure can initially be created with nano-carbon building blocks, optimized for the necessary morphological features of a specific application. Here, the synthesis and subsequent SiCNT/NW conversion of carbon nanotube spheres and graphene foam, demonstrates the ability to use a simple, cost-effective conversion method to create a material that can mechanically perform in extreme environments. Graphical abstract: Image 1